Legal Certainty of Tarim Cream Use: A Consumer Protection Law and Maqashid Sharia Perspective - Ababil, Bella; Alamudi, Ichwan Ahnaz; Abdillah, Muhammad Torieq; Umairoh, Noor Sifa (Journal of Islamic Economic Laws, 2025)
This study analyzes the legal certainty of Tarim cream under Consumer Protection Law and maqashid sharia principles. Tarim cream has gained popularity, particularly through social media promotion by religious influencers, despite lacking official BPOM and halal certification from BPJPH. This normative legal research employs a statutory and Islamic legal approach grounded in maqashid sharia. The findings reveal that Tarim cream violates consumer rights, particularly those related to safety, information transparency, and honest marketing. From the sharia perspective, the product potentially harms the five fundamental objectives of Islamic law: protection of religion, life, intellect, wealth, and lineage. This study underscores the need for stronger regulations and public education to ensure the circulation of halal and safe products in Indonesia. It contributes to strengthening consumer protection frameworks in the halal industry and emphasizes the importance of maqashid-based consumer awareness.